1997
DOI: 10.1007/pl00007584
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Interstitial Pneumonitis in Patients with Rheumatoid Arthritis by Measuring Circulating Levels of KL-6, a Human MUC1 Mucin

Abstract: In rheumatoid arthritis (RA), interstitial-pneumonitis is one of the major extraarticular complications that worsens a patient's prognosis. KL-6, a human MUC1 mucin, has been reported to be a sensitive serum marker for activity of interstitial pneumonitis. We investigated the clinical significance of serum KL-6 level in patients with RA. Serum levels of KL-6 and RA-associated inflammatory markers were evaluated in 177 RA patients. The diagnosis of active interstitial pneumonitis was made by clinical symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…However, because long-term use of steroids and/or immunosuppressants for underlying CTD induces severe susceptibility to infections or other adverse reactions, ineffectual and unnecessary therapy with these drugs must be avoided. In addition, the nature of multiple organ involvement makes it difficult to Studies of serum KL-6 level in CTD patients showed the increased levels in the patients with IP in general, when compared with healthy controls or CTD patients without IP (5)(6)(7)(8). These studies showed diverse levels for different patient groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, because long-term use of steroids and/or immunosuppressants for underlying CTD induces severe susceptibility to infections or other adverse reactions, ineffectual and unnecessary therapy with these drugs must be avoided. In addition, the nature of multiple organ involvement makes it difficult to Studies of serum KL-6 level in CTD patients showed the increased levels in the patients with IP in general, when compared with healthy controls or CTD patients without IP (5)(6)(7)(8). These studies showed diverse levels for different patient groups.…”
Section: Resultsmentioning
confidence: 99%
“…Upon epithelial breakdown, KL-6 is thought to leak into the circulation, where it can be measured by a commercially available ELISA kit. KL-6 has been studied extensively in mainly Japanese patients, where serum levels were found to be increased in various interstitial lung diseases such as radiation pneumonitis [22][23][24], CTD-associated lung disease [25][26][27] and drug induced pneumonitis [28]. Interestingly, KL-6 may have a role in fibrosis itself, as it was shown to induce proliferation of lung fibroblasts in vitro [29].…”
Section: Kl-6mentioning
confidence: 99%
“…However, these markers appear quite useful based on this study and previous studies (10,15) considering that the MTX penumonitis is sometimes fatal, even though MTX treatment is already standardized in RA therapy. Moreover, a recent prospective study reported that the occurrence of MTX pneumonitis could not be predicted by periodic pulmonary function testing (23 therefore, serum KL-6 and SP-D concentrations could be elevated prior to detection by pulmonary function testing, roentgenography and CT. Further prospective studies are required to determine whether or not these serum markers are useful in predicting the onset of MTX pneumonitis.…”
Section: Patientmentioning
confidence: 58%
“…The concentrations of serum KL-6 are significantly higher in patients with active lung disease than in those with inactive lung disease. For example, elevation of serum KL-6 concentration was detected in 88.9% of RA patients with active IP but in only 0.6% of those with inactive IP (15). It was demonstrated that concentrations of serum KL-6 may be dependent on alveolar-capillary permeability (16); moreover, proinflammatory cytokines such as tumor necrosis factor and interferon-y can augment the expression of KL-6 on type II pneumocytes (17).…”
Section: Patientmentioning
confidence: 99%